Komunikasi Estetik dalam Seni Pertunjukan Teater Rakyat Sandiwara Cirebon - Jaeni - - (LP2M ISBI Bandung, 2012)
ABSTRACT This research is aimed at studying aesthetic communication and its values in folk theatre per- formance, sandiwara Cirebon. This qualitative research with communication ethnography approach tries to scrutinize the event of sandiwara performance as communication event between the society in Cangkring village, Plered, Cirebon. The result shows that the aesthetic of sandiwara Cirebon has values, they are, feeling-experience values and socio-cultural values. Aesthetic values which are in- herent in the event of sandiwara Cirebon performance is an expression and reflection based on world views, beliefs, and values adopted by local people in the socio cultural life. To interpret those values, communication participant, artists, and public construct meaning of aesthetic communication based on communication context included in sandiwara Cirebon performance, namely contexts of intra- personal, public, culture, and transcendental. Keywords: Communication, Aesthetic, Ethnography, Performance, Theatre.